The Effect of Endorsement Korean, Brand Trust, and Social Media Marketing on Consumer Trust in Scarlett Products: The Moderating Role of Online Buying Experience - Sani, Della Tiara; Putri, Liestyaningrum Rahmadhani Wisnu (RISK : Jurnal Riset Bisnis dan Ekonomi, 2025)
This study aims to determine how online shopping experience affects the relationship between Korean endorsement, brand trust, and social media marketing with consumer trust in scarlett products. This study uses an online survey method with a sample of 200 respondents who have purchased scarlett products online. The results of the study indicate that online shopping experience moderates the relationship between Korean endorsement, brand trust, and social media marketing with consumer trust in scarlett products. This study also found that Korean endorsement, brand trust, and social media marketing have a positive influence on consumer trust in scarlett products. The independent variables studied are Korean Endorsement, Brand Trust, Brand Trust, and the moderating variable is Online Shopping Experience, while the dependent variable is Consumer Trust. Data analysis was carried out with the help of Smart PLS software with a purposive sampling technique. The results of this study can be used as a reference for companies in increasing consumer trust in scarlett products through effective marketing strategies.